2022
DOI: 10.1038/s41598-022-17628-8
|View full text |Cite|
|
Sign up to set email alerts
|

Traditional processing increases biological activities of Dendrobium offificinale Kimura et. Migo in Southeast Yunnan, China

Abstract: The orchid Dendrobium officinale grows throughout southeast China and southeast Asian countries and is used to treat inflammation and diabetes in traditional Chinese medicine. Tie pi feng dou is a well-known traditional Chinese medicine made from the dried D. officinale stems. Processing alters the physicochemical properties of TPFD; however, it is unclear how processing affects the quality and medicinal value of this plant. Here, we analyzed and compared the chemical composition of fresh stems of D. officinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…It was shown that traditional processing would change the contents of the key metabolites and improve the biological activities of DO [ 39 ]. Therefore, we further investigated the differences in monosaccharide composition between the FDOP and DDOP ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that traditional processing would change the contents of the key metabolites and improve the biological activities of DO [ 39 ]. Therefore, we further investigated the differences in monosaccharide composition between the FDOP and DDOP ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dendrobium has been used for anti-inflammation in traditional Chinese medicine. DOP, a key bioactive component of dendrobium, can inhibit oxidative stress and alleviate oxidative stress-induced damage 43 , 44 . These properties suggest that DOP may reduce oxidative stress-induced injury in the post-surgical environment.…”
Section: Discussionmentioning
confidence: 99%
“…The processing of TCM is a pharmaceutical technology based on the theory of TCM, syndrome differentiation, the inherent properties of drugs and the unique requirements for compounding and preparation. The purpose is to retain therapeutic ingredients while eliminating ineffective or potentially harmful ingredients (Zhou et al, 2022). TCM is mainly administered in the form of slices or pieces.…”
Section: Tcm Processingmentioning
confidence: 99%